PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS DAN SUPERVISI AKADEMIK TERHADAP DISIPLIN KERJA GURU SMP SE-KECAMATAN PAGARAN TP 2025/2026 - Romenak Hutasoit; Robinhot Sihombing; Berton Bostang H. Silaban (STKIP Subang, 2026)
This study aimed to: (1) Determine the influence of the principal’s democratic leadership style on teachers’ work discipline in junior high schools throughout Pagaran District in the 2025/2026 academic year; (2) Determine the influence of academic supervision on teachers’ work discipline in junior high schools throughout Pagaran District in the 2025/2026 academic year; and (3) Determine the simultaneous influence of the principal’s democratic leadership style and academic supervision on teachers’ work discipline in junior high schools throughout Pagaran District in the 2025/2026 academic year. This study employed a quantitative research method. The population consisted of all teachers from four public junior high schools in Pagaran District, North Tapanuli Regency, totaling 105 teachers. The sample size was determined using the Slovin formula with a margin of error of 0.05, resulting in 83 respondents. Data were collected through a closed-ended questionnaire consisting of 83 items. The results of data analysis revealed that: (1) The calculated F-value was greater than the F-table value for the relationship between democratic leadership style and teachers’ work discipline (414.426 > 3.07), indicating a positive and significant influence of democratic leadership style on teachers’ work discipline in junior high schools throughout Pagaran District, North Tapanuli Regency, with a contribution of 84.5%; (2) The calculated F-value was greater than the F-table value for the relationship between academic supervision and teachers’ work discipline (226.665 > 3.07), indicating a positive and significant influence of academic supervision on teachers’ work discipline in junior high schools throughout Pagaran District, North Tapanuli Regency, with a contribution of 74.9%; and (3) The calculated F-value was greater than the F-table value for the simultaneous influence of democratic leadership style and academic supervision on teachers’ work discipline (221.122 > 3.07), indicating a positive and significant simultaneous influence of democratic leadership style and academic supervision on teachers’ work discipline in junior high schools throughout Pagaran District, North Tapanuli Regency, with a contribution of 85.5%. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (H₀) was rejected.